2019
DOI: 10.3989/egeol.43587.550
|View full text |Cite
|
Sign up to set email alerts
|

First occurrence of <em>Cloudina carinata</em> Cortijo et al., 2010 in South America, Tamengo Formation, Corumbá Group, upper Ediacaran of Midwestern

Abstract: Se documenta en este resumen la primera aparición de Cloudina carinata Cortijo et al., 2010 en el continente americano. Esta nueva aparición extiende la distribución geográfica de esta especie, hasta ahora restringida a España y Siberia. Se presenta por primera vez en la Formación de Tamengo (Corumbá, Estado de Mato Grosso do Sul, Brasil) la asociación de metazoos mineralizados compuesta por Cloudina carinata, Cloudina lucianoi (Beurlen & Sommer, 1957) y Corumbella werneri Hahn et al., 1982. Esta asociaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…These ages agree with the 543 ± 3 Ma provided before by Babinski et al (2008). Furthermore, the presence of the indexfossils C. lucianoi and Cloudina carinata in the Tamengo Formation supports an upper Ediacaran age (Adôrno et al, 2017;Adôrno et al, 2019b).…”
Section: Frontiers Inmentioning
confidence: 78%
See 1 more Smart Citation
“…These ages agree with the 543 ± 3 Ma provided before by Babinski et al (2008). Furthermore, the presence of the indexfossils C. lucianoi and Cloudina carinata in the Tamengo Formation supports an upper Ediacaran age (Adôrno et al, 2017;Adôrno et al, 2019b).…”
Section: Frontiers Inmentioning
confidence: 78%
“…The "classical" facies of the Tamengo Formation are those observed in the Corcal section, which occur also in other outcrops of the region along the Paraguay river, such as in the sections of Porto Sobramil (also known as Claudio or Saladeiro), Cacimba, Porto Figueiras, Goldfish, Ladario-Corumbá escarpment, and Horii mine (Boggiani et al, 2010;Walde et al, 2015;Adôrno et al, 2019b;Oliveira et al, 2019;Rivera, 2019;Amorim et al, 2020). Alongside the same lithofacies, these sections display also consistent and rather homogenous δ 13 C values (Boggiani et al, 2010;Rivera, 2019;Caetano Filho, 2020;and this work).…”
mentioning
confidence: 96%
“…There are two specimens of Cl. carinata reported from the Tamengo Formation, Brazil [ 39 ]. Although slightly larger, they are similar in morphology to the types of this species from the Membrillar olistostrome (electronic supplementary material, figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…Due to similarity in the described collar structures, the species is suggested to be synonymized with C. hartmannae (Yang et al, 2016;Cai et al, 2017). On the other hand, Cloudina carinata, from the Villarta Limestone of the Ibor Group of Spain (Cortijo et al, 2010) and Tamengo Formation of Brazil (Adorno et al, 2019), is distinguished from C. hartmannae by its longitudinal crests. The putatively recrystallized Cloudina carinata in Siberia (Terleev et al, 2011) cannot be unequivocally confirmed by observations through thin-sections.…”
Section: Systematic Paleontologymentioning
confidence: 98%
“…hartmannae (Yang et al, 2016; Cai et al, 2017). On the other hand, Cloudina carinata , from the Villarta Limestone of the Ibor Group of Spain (Cortijo et al, 2010) and Tamengo Formation of Brazil (Adorno et al, 2019), is distinguished from C . hartmannae by its longitudinal crests.…”
Section: Systematic Paleontologymentioning
confidence: 99%